1993
DOI: 10.1063/1.353035
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of ZnSe films grown by migration enhanced epitaxy

Abstract: Articles you may be interested inStructure of Zn-Se-Te system with submonolayer insertion of ZnTe grown by migration enhanced epitaxy J. Appl. Phys. 99, 064913 (2006); 10.1063/1.2184434 CdSe/ZnSe quantum structures grown by migration enhanced epitaxy: Structural and optical investigations Appl.A comparative study of growth of ZnSe films on GaAs by conventional molecularbeam epitaxy and migration enhanced epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 16 publications
1
30
1
Order By: Relevance
“…The EPI 40 cm 3 the migration enhanced epitaxy technique [9], and then a 100-nm-thick ZnSe buffer was deposited. Cell temperatures of the Cd and Se sources were set at 200 and 178 1C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The EPI 40 cm 3 the migration enhanced epitaxy technique [9], and then a 100-nm-thick ZnSe buffer was deposited. Cell temperatures of the Cd and Se sources were set at 200 and 178 1C, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…MBE studies have reported a high density (10 8 cm Ϫ2 ) of stacking faults if the III-V surface was exposed initially to a flux of elemental Se, while exposure to a Zn flux prior to II-VI growth led to much lower stacking fault densities. 6,8,9 Based on reflection high energy electron diffraction ͑RHEED͒ results, this was associated with the nucleation of three-dimensional islands in the early stages of II-VI growth on Se-predosed surfaces as opposed to twodimensional growth on Zn-predosed surface. 5,6,8,9 However, a recent study of pseudomorphic ZnSe/GaAs͑001͒ heterostructures grown by metalorganic chemical vapor deposition reported an increase in the stacking fault density for heterostructures fabricated after exposure to Zn of the As-stabilized substrate, as well as for growth on surfaces on which excess As was present.…”
mentioning
confidence: 95%
“…Also, the FWHM of 320 arcsec is quite good for a film of this thickness. With no lattice matching (i.e., by doping), the narrowest rocking curve of ZnSe epitaxially grown on GaAs is 70-90 arcsec [8]. As film thickness increases the rocking curve width increases.…”
Section: Experimental Methodsmentioning
confidence: 98%